How Slight Solidification Rate Variations within Cast Plate Affect Mechanical Response: A Study on As-Cast A356 Alloy with Cu Additions - Maria Teresa Di Giovanni; Emanuela Cerri; Takeshi Saito; Shahid Akhtar; Petter Åsholt; Yanjun Li; Marisa Di Sabatino (Advances in Materials Science and Engineering)
The present work investigates a narrow range of secondary dendrite arm spacing (SDAS), in an as-cast A356 alloy with and without copper (Cu) additions. Cu was added to the base A356 alloy melt to reach the target concentration of 0.5 and 1 wt.%. Samples were selected from 3 different positions within the cast plate, offering 30, 35, and 40 μm SDAS variants. Tensile curves revealed a strong influence between the specimen cutting position and strength, with a pronounced effect in the Cu-containing alloys. Hardness measurements did not confirm the tensile response; hence, to understand the phenomenon, microstructural features have been investigated in detail. Eutectic silicon (Si) particle equivalent diameter (ED) size decreased from the top (T) to the bottom (B) position of the cast. Eutectic Si particle surface area (A%) was found to be denser at the B as compared to the T and simultaneously in the Cu-containing alloy as compared to the Cu-free reference alloy. Backscattered electron (BSE) images were employed to investigate the nature of the Cu-rich intermetallic phases. In conclusion, electrical conductivity measurements were performed to confirm the trends observed.